Norway : Financial Sector Assessment Program-Technical Note-Oversight and Supervision of Financial Market Infrastructure, and Selected Issues in the Payment System. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note reviews the oversight and supervisory framework for systemically important Financial Market Infrastructure (FMI) in Norway. Norway has a modern and stable FMI. The assessment results suggest an effective supervision and oversight framework supported by a strong legal basis, adequate oversight resources, and good domestic and foreign cooperation between authorities. All Norwegian FMIs have completed assessments against the new international standards and are in the process of improving observance where needed. The authorities could consider strengthening their cooperation to address the risks from outsourced critical infrastructures and tighter interdependencies across FMIs. The authorities could also consider additional measures to strengthen the operational resiliency of payment systems.